Transparent Dye-Sensitized Solar Cell Using Titanium Dioxide Thin Film - Kamaru Zaman, Siti Nur Yasmin; Ahmad, Mohd Khairul (Evolution in Electrical and Electronic Engineering, 2022)
On an FTO glass substrate, titanium dioxide (TiO2) thin films have been created and deposited. Utilizing the spin coating process, TiO2 solution is deposited on the substrate. TiO2 solution containing 5ml, 7ml, and 10ml TTIP that has been stirred overnight without pre-heating is used to create the TiO2 thin films. In a single hour, 450°C is used to anneal all thin films. Field Emission Scanning Electron Microscopy has been used to analyse the thin film’s surface morphology (FESEM). The X-Ray Diffraction (XRD) technique analysis, which revealed that the TiO2 thin film is in the nanocrystalline anatase phase, was used to demonstrate the crystallinity of TiO2. The optical transmittance of the thin films was measured using a UV-Vis spectrophotometer with a wavelength range of 300 nm to 1000 nm. UV filters out light. The sample can absorb a lot of light if there is a lot of light entering it. The DSSC’s performance increases as a result of its capacity to hold a lot of light. I-V measurements have been used to determine electrical characteristics. According to the results, increasing the film thickness can enhance dye molecule adsorption. According to the results of the trials, the TiO2 thin film with 7ml TTIP achieves the best efficiency, which is 0.0222%, when compared to 5ml & 10ml TTIP.